PENANGANAN DAN PERAWATAN PADA IBU MENYUSUI DENGAN MASTITIS DI BPM LUKLUATUN MUBRIKOH - Qurrotu Aini; Lelly Aprilia Vidayati (JURNAL PARADIGMA (PEMBERDAYAAN & PENGABDIAN KEPADA MASYARAKAT), 2019)
The risk of mastitis is one of the problems that occur during the breastfeeding process that affects the offering of breast milk (ASI). One of the factors that can increase the risk of mastitis incidence is breastfeeding technique. Based on the World Health Organization (World Health Organization) the estimated incidence of mastitis in breastfeeding mothers is around 12.6% -33% and the global prevalence is around 10%. Data on breastfeeding problems from April to June 2012 in Indonesia showed 22.5% had sore nipples, 42% of mothers had milk dams, 18% of mothers had blocked milk, 11% had mastitis, and 6.5% of mothers had breast abscesses. It was caused by the mother's mistake in breastfeeding her baby. Based on the data and information obtained from the midwife, Lukluatun, there were 20 breastfeeding mothers and 7 of them had mastitis. The method used to carry out community service is by collecting data on the number of post-partum mothers at BPM Luklutun Mubriqoh, then conducting interviews about mastitis knowledge in postpartum mothers, counseling about mastitis, and demonstrating breast care and treatment. Implemented at BPM Luklutun Mubrikoh. The luklutun midwife collaborated with STIkes Ngudia Husada Madura in an effort to find a solution so that the Maternity department offered a solution, namely conducting counseling on mastitis and training on the correct way of breastfeeding and breast care with mastitis.